Mechanically controlled quantum interference in graphene break junctions. Issue 12 (December 2018) - Caneva, Sabina; Gehring, Pascal; García-Suárez, Víctor; García-Fuente, Amador; Stefani, Davide; Olavarria-Contreras, Ignacio; Ferrer, Jaime; Dekker, Cees; Zant, Herre
Abstract The ability to detect and distinguish quantum interference signatures is important for both fundamental research and for the realization of devices such as electron resonators1, interferometers2 and interference-based spin filters3 . Consistent with the principles of subwavelength optics, the wave nature of electrons can give rise to various types of interference effects4, such as Fabry–Pérot resonances5, Fano resonances6 and the Aharonov–Bohm effect7 . Quantum interference conductance oscillations8 have, indeed, been predicted for multiwall carbon nanotube shuttles and telescopes, and arise from atomic-scale displacements between the inner and outer tubes9, 10 . Previous theoretical work on graphene bilayers indicates that these systems may display similar interference features as a function of the relative position of the two sheets11, 12 . Experimental verification is, however, still lacking. Graphene nanoconstrictions represent an ideal model system to study quantum transport phenomena13–15 due to the electronic coherence16 and the transverse confinement of the carriers17 . Here, we demonstrate the fabrication of bowtie-shaped nanoconstrictions with mechanically controlled break junctions made from a single layer of graphene. Their electrical conductance displays pronounced oscillations at room temperature, with amplitudes that modulate over an order of magnitude as a function of subnanometre displacements. Surprisingly, the oscillations exhibit a period larger than the graphene lattice constant. Charge-transport calculations show that the periodicity originates from a combination of the quantum interference and lattice commensuration effects of two graphene layers that slide across each other. Our results provide direct experimental observation of a Fabry–Pérot-like interference of electron waves that are partially reflected and/or transmitted at the edges of the graphene bilayer overlap region. Graphene mechanically controlled break junctions show room-temperature quantum interference effects as a function of sub-nanometre displacements.